Photolytic and photocatalytic activity of polyethylene glycol-capped zinc ferrite nanocomposites for the removal of sethoxydim herbicide residues in pond water - Ramaraju, K.; Rao, Tentu Nageswara; Prashanthi, Y.; Ganji, Parameswaram (Frontiers in Environmental Chemistry, 2025)
AimThis study examines the photolytic and photocatalytic activities of a polyethylene glycol-capped zinc ferrite nanocomposite aimed at removing sethoxydim herbicide residues from pond water.Material and MethodsZinc ferrite nanoparticles were produced using the sol-gel method with precursors like zinc nitrate and iron nitrate. A clear PEG solution was formed by dissolving 1 g of PEG in distilled water. PEG-ZnFe2O4 nanocomposites were synthesized by heating and calcining the mixture at 300 °C for 3 h. Polyethylene glycol capped zinc ferrite nanocomposites (PEG-ZnFe2O4 NCs) were characterized using various methods such as TEM, SEM, FT-IR, UV-Vis spectroscopy, and XRD. Two sets of spiked concentrations were prepared for experiments, one with the catalyst (PEG-ZnFe2O4) and the other without it. The samples were exposed to sunlight, collected at predetermined intervals, and filtered using a 0.45 μm PTFE membrane filter. The filtrates were collected into amber-colored vials before being validated using HPLC. The method validation process involved analyzing untreated control samples, working standard, and test solutions for method specificity, and calibration solutions were analyzed using HPLC at various concentrations.Results and DiscussionThe fortified samples were analyzed using the HPLC method to extract and quantify sethoxydim in pond water. The limit of quantification (LOQ) was established by performing five injections of recovery samples at a fortification level of 0.03 μg/mL for sethoxydim for low-level recovery. The limit of detection (LOD) was determined to be 0.01 μg/mL. The adsorption study assessed the effect of adsorbent dosage by mixing a 50 ml solution with various doses of PEG-ZnFe2O4 NCs. The study found that sethoxydim’s half-life in pond water without a catalyst was 4.80 days, while in the presence of a catalyst, it was 8.42 h.ConclusionWhen compared to photolysis, research on photocatalysis has revealed greater efficiency and quicker reactions, while the DT50 value, or half-life, holds considerable importance in environmental pond water. This study proposes new applications for PEG-ZnFe2O4 NCs in environmental remediation and waste water treatment.